Analysis of water resource management in tourism in China using a coupling degree model - Huaxian Liu (IWA Publishing, 2021)
With the rapid development of the tourism industry, the water resource consumption in tourism has largely increased and gets more complicated, making water resource management in tourism more difficult. To achieve sustainable water utilization in tourism, water resource management has to take full account of the local natural, social, and industrial conditions, both satisfying the demands of water resource protection and tourism development. To analyze this coupling relationship, an integrated index system comprised of 15 indices is designed, and a coupling degree model between tourism-related water resource management and local conditions is introduced. The result revealed that tourism-related water resource management is generally congruent with the local conditions in China, and provinces at the very high/low coupling stage presented four clusters. A discussion combining the change of water policies and the water use efficiency of hotels in Beijing revealed that water-saving policies are proven to be necessary for the tourism development. Furthermore, a discussion of the four clusters revealed the advanced experience and deficiency of water policies in substantial tourism areas. The results could provide references for the improvement of water policies in the tourism industry in China. Highlights An index system and a coupling degree model are introduced to analyze tourism-related water management and local conditions in China.; Water management in tourism is generally congruent with the local conditions in China, and their coupling relationship presented a cluster pattern.; Water-saving priority is necessary for tourism in China.; The provinces on the east coast should take the strictest water management in tourism.;